The Effectiveness of the Combined Use of Meropenem and Avibactam Against Carbapenemase-Producing Klebsiella pneumoniae Strains in an in vitro Dynamic Model - E. N. Strukova; M. V. Golikova; M. B. Kobrin; S. A. Dovzhenko; A. V. Golyshkin; N. R. Almyasheva; Yu. A. Portnoy (Антибиотики и Химиотерапия)
Background. Combinations of carbapenems with new-generation carbapenemase inhibitors are successfully used to combat infections caused by carbapenemase-producing Klebsiella pneumoniae strains. However, K. pneumoniae resistance to such combinations is already described. Therefore, the search for new antibiotic/inhibitor combinations is important. In this regard, meropenem/avibactam combination seems promising, with its effectiveness becoming the subject of the current study.The aim of this study was to evaluate the effectiveness of the combination of meropenem with the new carbapenemase inhibitor avibactam against carbapenemase-producing K. pneumoniae strains in an in vitro dynamic model.Methods. Two carbapenemase-producing strains, KPC (K. pneumoniae 28) and OXA-48 (K. pneumoniae 145), were exposed to meropenem or its combination with avibactam in the hollow fiber infection model that simulated the pharmacokinetic profiles of drugs in the human lung epithelial fluid. The following dosage regimens were simulated: 2000 mg of meropenem and 500 mg of avibactam as a 2-hour infusion every 8 hours during 5 days. The effect of the drugs on the total and resistant subpopulations of K. pneumoniae was evaluated by plating samples on agar media without and with meropenem at different MIC-fold concentrations.Results. Meropenem alone did not reduce the numbers of the total population and did not suppress the growth of resistant subpopulations of both strains, while combining meropenem with avibactam significantly reduced the total bacterial numbers and completely prevented the growth of resistant cells.Conclusion. The combination of meropenem/avibactam seems promising, due to the fact that it was characterized by high eﬃcacy and a lack of development of resistance to meropenem throughout the entire simulated course of therapy.